2016
DOI: 10.1021/acs.langmuir.6b02794
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interaction between a DNA Nucleotide (Adenosine-5′-Monophosphate Disodium) and Surface Active Ionic Liquids by Rotational Relaxation Measurement and Fluorescence Correlation Spectroscopy

Abstract: This article demonstrates the interaction of a deoxyribonucleic acid (DNA) nucleotide, adenosine-5'-monophosphate disodium (AMP) with a cationic surface active ionic liquid (SAIL) 1-dodecyl-3-methylimidazoium chloride (C12mimCl) and an anionic SAIL, 1-butyl-3-methylimidazolium n-octylsulfate ([C4mim][C8SO4]). Dynamic light scattering (DLS) measurements and 1H NMR (nuclear magnetic resonance) studies indicate that substantial interaction is taking place among the DNA nucleotide, AMP and the SAILs. Moreover, cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…In this review article, we summarize recent findings on DNA and IL interactions, with main focus on computational results. In contrast to several studies on the features and behavior of proteins and enzymes in aqueous ILs (see Benedetto and Ballone 2015; Egorova et al 2017;Smiatek 2017;Schröder 2017; Zhao 2015b for a detailed overview), DNArelated studies were only sparsely conducted, and most of the research carried out to date relies on experimental procedures (Cheng et al 2007;Xie et al 2008;Singh et al 2012;Araújo et al 2013;Sharma et al 2015;Roy et al 2016;Pandey et al 2018) instead of simulation approaches. Despite limitations in the used force fields and models (Dommert et al 2012;Zeman et al 2017;Uhlig et al 2018), the benefits of computer simulations rely in their ability to provide a detailed level of information, which is often not reachable even by advanced experimental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In this review article, we summarize recent findings on DNA and IL interactions, with main focus on computational results. In contrast to several studies on the features and behavior of proteins and enzymes in aqueous ILs (see Benedetto and Ballone 2015; Egorova et al 2017;Smiatek 2017;Schröder 2017; Zhao 2015b for a detailed overview), DNArelated studies were only sparsely conducted, and most of the research carried out to date relies on experimental procedures (Cheng et al 2007;Xie et al 2008;Singh et al 2012;Araújo et al 2013;Sharma et al 2015;Roy et al 2016;Pandey et al 2018) instead of simulation approaches. Despite limitations in the used force fields and models (Dommert et al 2012;Zeman et al 2017;Uhlig et al 2018), the benefits of computer simulations rely in their ability to provide a detailed level of information, which is often not reachable even by advanced experimental procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Anionic DNA nucleotide adenosine-5′-monophosphate disodium (AMP) also forms supramolecular assembly. It is reported that the micellar aggregates of imidazoliumcontaining SAILs, C 12 mimCl and [C 4 mim][C 8 SO 4 ], can transform into larger micellar assemblies interacting with anionic DNA nucleotide AMP (Roy et al 2016a). Interestingly, the micellar aggregates of C 16 mimCl convert to vesicular assembly with increase in the concentration of organic additive 5-methyl salicylic acid (5-ms).…”
Section: Sail/biomolecules Assemblymentioning
confidence: 99%
“…48 Beside 5 ms, DNA nucleotide AMP (adenosine-5/-monophosphate) also induces the formation of larger micellar aggregates composed of cationic (C 12 mimCl) and anionic ([C 4 mim][C 8 SO 4 ]) surfactants (Figure 4c). 77 However, the insertion of negatively charged AMP into the cationic surfactant is more prominent compared to that of anionic surfactants. Therefore, the tunable micelle− vesicle transition and concomitant viscosity increase upon heating have utility in a range of areas, including microfluidics, controlled release, and oil recovery.…”
Section: Fatty Acidmentioning
confidence: 99%
“…Image (a) is reproduced with permission from ref (copyright 2006, American Chemical Society). Images (b) and (c) are reproduced from ref (copyright 2016, American Chemical Society) and ref (copyright 2016, American Chemical Society).…”
Section: Classification Of Vesiclesmentioning
confidence: 99%